Comparative construct validity of three presenteeism instruments in workers with musculoskeletal complaints: a prospective cohort study. Issue 2 (31st August 2020) - van der Burg, Lennart; Sepriano, Alexandre; Landewé, Robert; Geuskens, Goedele; Ottenheijm, Ramon; Dinant, Geert-Jan; Boonen, Annelies
Abstract : Objectives: To compare the construct validity of three presenteeism instruments, using health and economic outcomes as external references, among working persons reporting musculoskeletal complaints. Methods: Data from the prospective Study on Transitions in Employment, Ability and Motivation were used. Presenteeism measurement comprised a global rating of work-ability, and two instruments indicating at-work productivity, and was assessed yearly over 6 years of follow-up. Longitudinal associations between measures of health and subsequent presenteeism, and between presenteeism and subsequent days of sick leave were assessed using generalised estimating equation models. The effect of groups of contextual factors (socio-demographic, lifestyle, personal and work-related factors) was investigated by assessing the change in explained variability. Results: In total, 4523 persons were analysed. The association between physical health and work-ability was stronger than both at-work productivity measures; 10 points increase in physical health (0–100, higher is better) was associated with 0.79 points (95% CI 0.75 to 0.84) better work-ability (0–10, higher is better) in the subsequent year. Besides, work-ability best predicted sick leave; one point higher work-ability was associated with 4 days less sick leave (95% CI −5.09 to −3.63) the subsequent year. Personal factors improved model fit for models on health and work-ability, but conflicting results were seen for both at-work productivity instruments. Conclusion: Work-ability showed higher construct validity against health and economic outcomes as compared to at-work productivity, which shows that work-ability is different to productivity (losses). Personal factors are especially relevant when interpreting the relation between health and work-ability or self-reported quantity of work.